Bioanalytical approaches for characterizing catabolism of antibody–drug conjugates. (July 2015) - Saad, Ola M; Shen, Ben-Quan; Xu, Keyang; Khojasteh, S Cyrus; Girish, Sandhya; Kaur, Surinder
The in vivo stability and catabolism of antibody–drug conjugates (ADCs) directly impact their PK, efficacy and safety, and metabolites of the cytotoxic or small molecule drug component of an ADC can further complicate these factors. This perspective highlights the importance of understanding ADC catabolism and the associated bioanalytical challenges. We evaluated different bioanalytical approaches to qualitatively and quantitatively characterize ADC catabolites. Here we review and discuss the rationale and experimental strategies used to design bioanalytical assays for characterization of ADC catabolism and supporting ADME studies during ADC clinical development. This review covers both large and small molecule approaches, and uses examples from Kadcyla ® (T-DM1) and a THIOMAB™ antibody–drug conjugate to illustrate the process.